The Association between the Extend of Burn Injuries with Albumin Level on Burn Injury patients - Matondang, Adetya Indah Sari; Desiree Anggia Paramita (Talenta Publisher, 2020)
Abstract. Burn injuries is a damaged or loss of skin caused by a contact with either high temperature sources or very low temperature sources. Burn injuries is classified according to its etiology, depth and extend of the wound. The extend of the burn can be determined by calculating TBSA (Total Body Surface Area). Wider TBSA will cause lower serum albumin levels due to a higher percentage increase. The purpose of this study was to determine the association between the extend of burn injuries with albumin levels on burn injury patients at Haji Adam Malik General Hospital Medan in 2017-2018. This research uses observational research with cross-sectional research design, using secondary data obtained from medical records at Haji Adam Malik General Hospital Medan in 2017-2018. The research sample was selected by using the total sampling method from all medical record data that met the research criteria. In this study, significant results were obtained with a value of p = 0.006 (p < 0.05) between the extend of ​​burn injuries and albumin levels in burn injury patients at Haji Adam Malik General Hospital Medan in 2017-2018. Keyword: Burn injury, Albumin, TBSA, RSUP Haji Adam Malik, Medan